1979
DOI: 10.1136/jech.33.3.171
|View full text |Cite
|
Sign up to set email alerts
|

The influence of availability of free school milk on the height of children in England and Scotland.

Abstract: SUMMARY The effect is investigated of availability of free school milk on height gain in one year of six-and seven-year-old primary schoolchildren in England and Scotland, using data collected annually from 1972 to 1976. The height gain of children for whom milk was available for the whole year of observation was compared with that of children who had no milk. Out of 16 sex-country-year-specific analyses for children from manual social classes only, 13 showed no significant evidence of greater height gain in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Grillenberger et al [15] found no difference in growth between schoolchildren supplemented with milk compared to meat in a Kenyan study. In a study with 6-to 7-year-old children conducted in England and Scotland, Cook et al [16] found that children with free access to milk did not grow more than those with no access. Some intervention studies have examined the effect of dairy products on bone growth [17].…”
Section: Milk and Growthmentioning
confidence: 99%
“…Grillenberger et al [15] found no difference in growth between schoolchildren supplemented with milk compared to meat in a Kenyan study. In a study with 6-to 7-year-old children conducted in England and Scotland, Cook et al [16] found that children with free access to milk did not grow more than those with no access. Some intervention studies have examined the effect of dairy products on bone growth [17].…”
Section: Milk and Growthmentioning
confidence: 99%
“…Rona and Chinn (1989) reported no consistent association between milk provisioning in schools and rates of growth in three samples of children of age 5-10, even when stratified by poverty status and ethnic background. Likewise, Cook et al (1979) investigated height gains among a very large sample of 6-to 7-year-old schoolchildren, and found that those with access to free milk did not grow significantly more in height than those without such access, even when socioeconomic status was accounted for. The number of glasses of milk drunk did not predict height gain in any group.…”
Section: Milk Composition In Relation To Growthmentioning
confidence: 99%
“…Wiley showed that younger children in the highest quartile of dairy intake had a higher body mass index (BMI) than those in the lowest two quartiles [19]. On the other hand, several studies did not support the association between ASF consumption and the physical growth of the child [20,21]. In an Indonesian study, milk consumption showed a significantly negative association with a child classified as underweight or stunted, but not with wasted children; meanwhile, the consumption of meat/poultry and eggs revealed no significant impact on all the z scores [22].…”
Section: Protein-based Food (Bpf) In the Food Intervention Programmentioning
confidence: 99%